Safe and Rapid Synthesis and Utilization of 2-Azidopyridine and Related Derivatives via Continuous Flow Diazotization - Szemesi, Péter; Bana, Péter; Szakács, Zoltán; Greiner, István; Éles, János (Current Organic Chemistry, 2022)
Aril azides are popular reagents in the laboratory, but their explosive properties prevent their larger-scale application. The safety risk is even greater for N-heterocyclic azides, which are rarely studied. Flow chemistry can be an effective tool in the synthesis and utilization of dangerous and explosive chemicals. In small-diameter flow reactors, good heat and mass transfer prevent local hot spots and side reactions, and since only small amounts of hazardous chemicals are present at any time, the potential danger is reduced in the event of an accident. In this work, the safe syntheses of 9 different 2-azidopyridine, 2-azidopyrimidine and 2-azidoquinoxaline derivatives were successfully achieved within the continuous-flow system. In most cases, simple work-up resulted in pure products. In-line extractive work-up was also implemented, which allowed us to transform 2-azidopyridine in a subsequent Staudinger reaction in a connected flow reactor, without manual handling of the hazardous azide.
Keywords: Flow chemistry